Eliminating the Gap of Labor and Social Protection for the Workers of Platform-Based Transportation - Silaban, Rekson; Ghafur, Hanief Saha; Widiawaty, Dyah; Basir, Basir (Faculty of Law, Universitas Sebelas Maret, 2023)
This study aims to examines online transport business practices in Indonesia and assesses whether workers get decent labor protection. The study tries to provide the answer to the unresolved debate about what form of regulation to close the protection for platform work. The method used a descriptive-qualitative research design with the study case paradigm notably in online transportation sectors. Research data was obtained through in-depth semi-structured interviews with drivers from different apps in Jakarta, the Indonesia Capital City. The study found that the improvement of employment protection for workers can only be done by first clarifying the legal status of workers, and determining the form of employment protection that is suitable for them, which is made through a special regulation. The study proposes a way out by providing options based on selected countries experiences of different continents on how the platform should protected without hurting platform business.